OPTIMISING THE ROLE OF CREATIVE ECONOMY IN SOCIETY THROUGH LITERATURE REVIEW: EMPOWERMENT STRATEGIES AND SUSTAINABLE DEVELOPMENT MODELS - Moh. Yamin Darsyah; Sidderatul Akbar; Widjanarko; Al-Amin (Adiba Aisha Amira, 2023)
The creative economy is an economic sector that generates value through intellectual creation and innovation. It encompasses a range of economic activities related to the creation, production, and distribution of goods and services based on knowledge and creativity. The creative economy empowers individuals by prioritising talents, skills, and creative ideas that contribute to job creation, economic growth, and social and cultural development. The research method conducted in this study is the literature research method. The results show that creative economy empowerment can be done through three main strategies: education and training oriented towards creativity and innovation; development of infrastructure and ecosystems that support synergies between creative economy actors; and utilisation of technology and digital platforms to expand market access. Moreover, a sustainable development model in the creative economy must incorporate elements of economic, social and environmental sustainability. This research reinforces the understanding that the creative economy must be managed with strategies that include sustainable development principles to realise wider benefits for society and the environment.